Study on the architectural design of a new type of waste incineration power plant based on NIMBY effect. Issue 1 (July 2021) - Yuanyuan, Li
Abstract: With the development of economy and urbanization, facing the dilemma of "garbage besieged city", China's "fourteenth five year plan" continues to focus on development and ecological protection. Waste incineration power generation is the most environmentally-friendly and efficient means of waste treatment. However, facilities such as waste incineration power plant are often faced with the problem of "NIMBY effect". Through the analysis of typical cases at home and abroad, combined with the project practice of Foshan Gaoming District waste incineration power plant, this paper explores how to alleviate the NIMBY effect through architectural design from three aspects of appearance design, ancillary functions and external environment.